Digital finance and agri-food value chains: Case studies from Ethiopia - Wassie, Solomon (International Food Policy Research Institute, 2025)
Agriculture is of paramount importance to Ethiopia’s economy. Agriculture accounts for 40 percent of the country's GDP, 80 percent of export earnings, and employs 75 percent of the population (Tamene & Ali, 2022). Crop and livestock production account for roughly 65 percent and 25 percent of agricultural GDP, respectively (International Trade Administration, 2024). Cereals account for roughly 90 percent of total grain production. Teff, known for its gluten-free nutritional aspect, takes the leading share of cereals by production area (ESS 2022). Ethiopia is also the second-largest wheat producer in Africa, following South Africa, with an expansion potential of 1.3 million hectares (Senbeta & Worku, 2023). Coffee, a crop with high cultural and economic importance in Ethiopia, accounts for 30 percent of exports and 25 percent of total employment. Ethiopia stands as Africa's leading coffee producer and among the top five coffee producing nations worldwide (Tefera & Torry, 2023).